Cultural Differences in Inhibitory Control: An ALE Meta-Analysis - Gavazzi, Gioele; Noferini, Chiara; Benedetti, Viola; Cotugno, Maria; Giovannelli, Fabio; Caldara, Roberto; Mascalchi, Mario; Viggiano, Maria Pia (Brain sciences, 2023)
Culture greatly influences our attitudes, beliefs, and behaviors, affecting how we communicate and make decisions. There is an ongoing debate regarding the belief that people from Eastern cultures possess greater self-control abilities when compared to people from Western cultures. In this study, we conducted a meta-analysis using the Activation Likelihood Estimation (ALE) algorithm to compare 30 studies (719 subjects, 373 foci) that used fMRI to investigate the performance in Go–Nogo and Stop Signal Tasks of participants from Western and/or Eastern countries. Our meta-analysis found differences between the networks activated in Eastern and Western culture participants. The right prefrontal cortex showed distinct patterns, with the Inferior Frontal gyrus more active in the Eastern group and the middle and superior frontal gyri more active in the Western group. Our findings suggest that Eastern culture subjects have a higher tendency to activate brain regions involved in proactive inhibitory control, while Western culture subjects rely more on reactive inhibitory brain regions during cognitive control tasks. This implies that proactive inhibition may play a crucial role in promoting the collective and interdependent behavior typical of Eastern cultures, while reactive inhibition may be more important for efficient cognitive control in subjects of Western cultures that prioritize individualism and independence.